Standardized extract of Mangifera indica L. leaves as an antimycobacterial and immunomodulatory agent - Shailajan, Sunita; Menon, Sasikumar; Kulkarni, Savita; Tiwari, Bhavesh (Pharmacognosy Communications)
Background: Mangifera indica L.; the largest fruit-tree found in India, is an important component of indigenous medical systems. Mangifera indica L. leaves (MIL) have been reported to possess various biological activities and thus, can be a useful source of substances for drug development. Although the leaves have been traditionally used as antibacterial and immunomodulatory agent, there is a paucity of scientific data in support of their efficacy. The purpose of this study was an in-depth evaluation of antimycobacterial and immunomodulatory activity of a standardized extract of MIL. Material and Methods: The hexane extract of Mangifera indica L. leaves (HEMIL) was prepared and standardized. Chromatographic char- acterization of HEMIL was done using validated HPLC and GC-MS/MS technique. HEMIL was evaluated for antimycobacterial and immunomodu- latory activity by using various in vitro and in vivo assays. Results and Discussion: HEMIL showed lupeol and stigmasterol content of 21.04 ± 0.03 mg/g and 16.99 ± 0.04 mg/g, respectively; and total terpenoids con- tent of 112.55 ± 2.16 mg LE/g. GC-MS/MS characterization of the extract confirmed the presence of lupeol and stigmasterol and revealed five other phytochemical constituents. The safety of HEMIL was established in vitro and in vivo. HEMIL showed concentration-dependent inhibition of MTB as evident in REMA and radiorespirometry. HEMIL was also found efficacious in immunomodulatory evaluations using RAW 264.7 cells, human PBMCs, cyclophosphamide induced myelosuppressed mice and SRBCs stimulated mice. Conclusion: The promising results not only support the traditional claim of MIL as antibacterial and immunomodulatory agent but also provide data on their use in food supplements for immuno-pharmacological use.
Keywords: Mangifera indica L. Leaves; Triterpenoids; Chromatography; Safety; Efficacy.